Analisis Finansial dan Kelayakan Usaha Industri Rumah Tangga Ikan Asin Bapak Aris di Kelurahan Sumber Jaya Kecamatan Kampung Melayu Kota Bengkulu - Wijayanti, Vivie; Nurmalia, Ana; Yumiati, Yossie (VISA: Journal of Vision and Ideas, 2026)
Salted fish is a food product made from fish meat preserved by adding salt. Through this preservation method, fish meat, which would normally spoil within a short time, can be stored at room temperature for several months, although it usually needs to be tightly sealed. The purpose of this study is to determine the financial analysis and business feasibility of Mr. Aris’s household-scale salted fish industry located in Sumber Jaya Village, Kampung Melayu District, Bengkulu City. The research method used is a descriptive qualitative and quantitative approach by applying financial and business feasibility analysis. The results show that Mr. Aris’s household salted fish industry is feasible to be continued. The financial analysis of the salted fish processing business in Sumber Jaya Village, Kampung Melayu District, Bengkulu City indicates that the business generated total revenues in 2021, 2022, and 2023 of Rp 187,300,000; Rp 250,900,000; and Rp 409,750,000, respectively, while the total costs in 2021, 2022, and 2023 amounted to Rp 145,728,000; Rp 192,156,000; and Rp 302,510,710, respectively. The feasibility levels differ each year, with a Benefit–Cost Ratio (B/C) of 1.28 in 2021, 1.30 in 2022, and 1.35 in 2023. Since the Benefit–Cost Ratio is greater than one (B/C > 1), the project is considered feasible to implement in each of these years. The business feasibility analysis of the salted fish industry in Sumber Jaya Village, Kampung Melayu District, Bengkulu City also shows positive Net Present Value (NPV) results each year, namely Rp 45,728,742.71 in 2021, Rp 71,084,220.716 in 2022, and Rp 142,738,306.934 in 2023. Since the NPV values are greater than zero (NPV > 0), the project is considered feasible to be implemented. The Internal Rate of Return (IRR) value is 62.71%, indicating that the annual rate of return on the total invested capital in the project is 62.71%. This value is higher than the established discount rate of 10%; therefore, based on the IRR criterion, the project is declared feasible to be implemented.